2015
DOI: 10.1038/nn.4188
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing APP and BACE-1 approximation in neurons yields insight into the amyloidogenic pathway

Abstract: Cleavage of APP (amyloid precursor protein) by BACE-1 (β-site APP cleaving enzyme-1) is the rate-limiting step in amyloid-beta (Aβ) production and a neuropathologic hallmark of Alzheimer's disease (AD); thus physical approximation of this substrate-enzyme pair is a critical event with broad biological and therapeutic implications. Despite much research, neuronal locales of APP/BACE-1 convergence and APP-cleavage remain unclear. Here we report an optical assay – based on fluorescence complementation – to visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
169
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(187 citation statements)
references
References 46 publications
(81 reference statements)
18
169
0
Order By: Relevance
“…Consistent with the data of others (Das et al , 2016), FL‐APP and BACE1 co‐migrated partially with a marker for endosomes (Rab7), but not with lysosomal, ER‐intermediate, or MAM markers (Fig 2C). Similarly, the APP‐CTFs C83 and C99 co‐migrated with endosomal and lysosomal markers (Rab5, Rab7, and LAMP‐2) (Haass et al , 2012; Das et al , 2016), whereas PS1 co‐migrated with MAM markers, such as FACL4 (Area‐Gomez et al , 2009; Newman et al , 2014; Schreiner et al , 2015). We reasoned that the difficulty in seeing APP‐CTFs and PS1 together was probably due to the rapid cleavage of the CTFs by γ‐secretase once both are in the same compartment.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with the data of others (Das et al , 2016), FL‐APP and BACE1 co‐migrated partially with a marker for endosomes (Rab7), but not with lysosomal, ER‐intermediate, or MAM markers (Fig 2C). Similarly, the APP‐CTFs C83 and C99 co‐migrated with endosomal and lysosomal markers (Rab5, Rab7, and LAMP‐2) (Haass et al , 2012; Das et al , 2016), whereas PS1 co‐migrated with MAM markers, such as FACL4 (Area‐Gomez et al , 2009; Newman et al , 2014; Schreiner et al , 2015). We reasoned that the difficulty in seeing APP‐CTFs and PS1 together was probably due to the rapid cleavage of the CTFs by γ‐secretase once both are in the same compartment.…”
Section: Resultssupporting
confidence: 92%
“…Confocal microscopy analysis revealed that C99 (in red) was present mainly in the cytosol and in ER membranes (in green), as shown previously by others (Das et al , 2016). In addition to those sites, C99 (in red) also colocalized with regions where both ER (in green) and mitochondria (in blue) were present (white arrows in Fig 2E and Appendix Fig S2D).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were obtained for neurons transfected with BACE1-mRFP1 (Fig. 3-15, B), a protease that helps produce amyloid-β (Αβ) from the amyloid precursor protein (AβPP), and has been shown to be trafficked along with APP by kinesin-1 [252]. BACE1-mRFP1 expressing neurons treated with oligomeric tau showed an ~2-fold increase in anterograde run length and a ~40% increase in anterograde instantaneous velocity, suggesting that oligomeric 2N4R tau treatments affect multiple kinesin-1 cargoes in the same general manner.…”
Section: Accumulation Of Endogenous Axonal Tau Is Associated With Dyssupporting
confidence: 73%
“…To analyze the effect, if any, that the mislocalization of tau we describe here has on axonal transport, primary neurons were transfected with fluorescently-tagged proteins to label vesicles undergoing microtubule-directed fast axonal transport. Specifically, BDNF-mRFP1 and BACE1-mRFP1 were utilized to analyze effects on kinesin-1-dependent transport [103,252], and NeuropeptideY-mCherry to observe kinesin-3-dependent transport [103] (see Supplementary movie 1). Because 2N4R tau oligomers produced a robust response in previous experiments and data analysis for these experiments was extremely time consuming, we focused only on 2N4R tau oligomers.…”
Section: Accumulation Of Endogenous Axonal Tau Is Associated With Dysmentioning
confidence: 99%